The Treatment of African-American Female Students in an Urban School District in the Midwestern United States - Martin, Don; Martin, Magy (European Scientific Journal, ESJ, 2021)
This research project examined the unfair treatment and disciplinary actions for African-American female students in an urban school district. The authors studied students in grades nine through 12 in both an early college high school and a traditional high school. Results indicated that AfricanAmerican female students are often treated as older than they were and sexually more mature than female Caucasian students. In addition, the suspension and disciplinary rates were abnormally high in our African American population.